Evaluación del curado de resinas fenólicas tipo novolaca modificadas con lignina por espectroscopia infrarroja por transformada de fourier - Martínez, Juan David (2009)
Phenol is an expensive and toxic raw material derived from petroleum, for these reasons, it’s necessary to take a look for alternative materials in order to replace it. Lignin represents a good choice, especially in phenolic resins obtained from the polycondensation reaction between formaldehyde and an excess of phenol. As an analytical technique for the curing study, the Fourier transform infrared spectroscopy (FT-IR) was used. Unmodified novolac resin (PF) and four lignin modified resins were analyzed. Lignin modified resins correspond to: lignin isolated at pH4 (PFL), lignin isolated at pH2 (PFLpH2), phenolated lignin (PFLFen) and demethylated lignin (PFLDes). Samples were cured at two different concentrations of HTMA. Curing analysis includes conversion curves. According with these results, non-significant variations on final conversion of PFLFen respect to PF were observed. For other resin samples, reductions on the final conversion were observed. On the other hand for all samples, when the weight percentage of HMTA increases reductions on the cure conversion were observed.